(untitled) (Филолошке студије, 2021)
The article describes the design of a diachronic terminological database of Slovenian linguistic terminology. The multilingual terminological database will include extensive information about linguistic terms (standardized written form, attested forms, pronunciation, synonyms, attested definition, idealized definition, detailed information on the concept, information on the grammar and the author of the grammar, bibliographic data). The article also contains a sample term record of the designed Diachronic Database of Slovenian Linguistic Terminology, i.e. the term ime ‘noun’ from Valentin Vodnik’s grammar Piſmenoſt ali Gramatika sa Perve Shole (1811).